Pendekatan Eksperimen Karakteristik Respon Getaran Sistem Two Degree of Freedom dengan Penambahan Independent Dual Dynamic Vibration Absorber - Susastro Susastro; Novi Indah Riani (Universitas Muhammadiyah Sidoarjo, 2018)
Vibration is one of the problems that must be reduced in a vehicle. There are many ways to reduce vibration in vehicles, one of them is by adding Dynamic vibration absorber (DVA). While Dual Dynamic vibration absorber (dDVA) is a DVA period that is able to move in the translational direction given to the system to reduce translation vibration and when there is resonance. Translation DVA is an additional type of time used to reduce the vibration of the translation direction. So far there is not much research related to the use of translational DVA to reduce rotational vibrations as well as translation. In this study, a study was conducted related to the use of independent double translational DVA (dDVA) to reduce translation vibrations as well as rotation of the beam. The research was conducted by modeling the system obtained into mathematical equations and simulations were carried out to determine the characteristics of vibrations that arise. In the simulation, one of the DVA periods is placed at the center of the main system period, while the other DVA period is given a change between the center period and the end of the system. The results of the study show that the maximum reduction in translational vibration is 95.51% and occurs when the absorber is placed at the center of the system, while the maximum rotation vibration reduction is 56.62% and is obtained when the system is given with an arm ratio of 1 and zero.